Comparison of magnetic resonance feature tracking with CSPAMM HARP for the assessment of global and regional layer specific strain. (1st October 2017) - Kuetting, Daniel L.R.; Feisst, Andreas; Dabir, Darius; Homsi, Rami; Sprinkart, Alois M.; Luetkens, Julian; Schild, Hans H.; Thomas, Daniel K.
Abstract: Purpose: Layer specific strain assessment is increasingly being employed clinically. Cardiac magnetic resonance (MR) Feature Tracking (FT) is considered to be an adequate alternative for strain assessment. The aim of this study is to investigate the feasibility of FT derived layer specific strain assessment. Methods: CSPAMM and SSFP-Cine sequences were acquired in 38 individuals (19 patients with HFpEF, 19 controls) in identical midventricular short-axis locations. Global endocardial-, midmyocardial-, epicardial- peak systolic circumferential strain (PSCS) and regional epicardial PSCS were calculated and intra- as well inter-observer variability were assessed. Results: FT derived global epicardial and endocardial PSCS (7.9 ± 2.3%; − 19.6 ± 4.9%) were significantly lower than tagging derived global epicardial and endocardial PSCS (− 13.2 ± 2.8%; − 32.3 ± 5.9%) (each p < 0.001), while FT derived endocardial PSCS and tagging derived midmyocardial PSCS showed a strong correlation (r = 0.71) and no significant differences. Global intra- and inter-observer variability of FT derived endocardial PSCS circumferential measures were acceptable (coefficient of variation 6.5% and 5.7%) while reproducibility of epicardial PSCS (coefficient of variation 16.8% and 18.1%) was poor. Conclusion: The FT algorithm allows for reliable assessment of midmyocardial strain, while underestimating epicardial and endocardial strain and delivering less reproducible results than the gold standard of tagging.